Cultural selection: The Shanfari as a model - Hashem, Nibras (Al-Adab Journal, 2019)
This research deals with identity as a relationship of attraction and conflict between the ego and the other, the ego with the other individual at times, and the ego with the other group at other times, and it is not natural to deny the existence of these conflicts .And identity also as a product of the relationship of the ego or the present group now, with the past (we), so we find that in the study of poetry before Islam, a renewed cultural value, especially the poetry of the Saaliks and their struggle with the tribe; Saalouk represents the identity of the non-member and its roots in the Arab mind.Sallagh is a phenomenon that was invented at the time, and was chosen for social and economic reasons, but it disappeared with the end of its causes, then it was returned in different stages of the Arab history, and if its names change with the variables of each era, it is a cultural phenomenon that is elected and spread, and may also disappear with the disappearance of its causes. This election for the social phenomenon is matched by another type of election. It is a cultural election by choosing their poetry and news in the monetary blog, past and present, because of its cultural value in collective.